Pengembangan Media Kuku Pesek Berbasis Digitalisasi untuk Meningkatkan Pengetahuan Pendidikan Seksual Anak Usia 5-6 Tahun di TK Khalifah 16 Palembang: Penelitian - Fakhirah Rianti; Leny Marlina; Kurnia Dewi (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This research is motivated to introduce early sexual education, especially for children aged 5-6 years in Khalifah 16 Kindergarten, Palembang, because of the low knowledge about sexual education, because teachers only use children's worksheets, so that children are not interested and do not get direct experience in the learning process. The purpose of this study is to develop Kuku Pesek media based on digitalization that is valid, practical, and effective in increasing sexual education knowledge in children aged 5-6 years. The method used is Research and Development with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) research model. The subjects of this study were group B at Khalifah 16 Kindergarten, Palembang. The initial field trial stage was carried out with 10 students and the main field trial with all group B at Khalifah 16 Kindergarten, Palembang, which was 20 students. Data collection techniques using observation, questionnaires, documentation and interviews. Data analysis techniques using validity tests, practicality tests, and effectiveness tests. Validity, practicality, and effectiveness data were obtained based on questionnaire response data analyzed using a Likert scale. The results of the study showed the validity of material experts 92.5 in the very valid category and design experts 93.3 in the very valid category. The practicality test of the dressing frame media based on the teacher response questionnaire 93 in the very practical category, and the student response questionnaire was carried out in the form of an instrument stated that it was very effective in the initial field trial 74.0625 stated effective, and in the main field trial 92.34 stated very effective. So it can be said that there is a significant difference in children before and after receiving treatment. The results of this study conclude that the digitalization-based flat nail media to improve sexual education knowledge is stated to be valid, practical, and effective for use in learning.